The mitochondrial DNA G13513A MELAS mutation in the NADH dehydrogenase 5 gene is a frequent cause of Leigh-like syndrome with isolated complex I deficiency. Issue 3 (1st March 2003) - Chol, M; Lebon, S; Bénit, P; Chretien, D; de Lonlay, P; Goldenberg, A; Odent, S; Hertz-Pannier, L; Vincent-Delorme, C; Cormier-Daire, V; Rustin, P; Rötig, A; et al.
Abstract : Leigh syndrome is a subacute necrotising encephalomyopathy frequently ascribed to mitochondrial respiratory chain deficiency. This condition is genetically heterogeneous, as mutations in both mitochondrial (mt) and nuclear genes have been reported. Here, we report the G13513A transition in the ND5 mtDNA gene in three unrelated children with complex I deficiency and a peculiar MRI aspect distinct from typical Leigh syndrome. Brain MRI consistently showed a specific involvement of the substantia nigra and medulla oblongata sparing the basal ganglia. Variable degrees of heteroplasmy were found in all tissues tested and a high percentage of mutant mtDNA was observed in muscle. The asymptomatic mothers presented low levels of mutant mtDNA in blood leucocytes. This mutation, which affects an evolutionary conserved amino acid (D393N), has been previously reported in adult patients with MELAS or LHON/MELAS syndromes, emphasising the clinical heterogeneity of mitochondrial DNA mutations. Since the G13513A mutation was found in 21% of our patients with Leigh syndrome and complex I deficiency (3/14), it appears that this mutation represents a frequent cause of Leigh-like syndrome, which should be systematically tested for molecular diagnosis in affected children and for genetic counselling in their maternal relatives.